Mathematical Communication Ability Assessed By Student Self- efficacy In Learning The Two Stay Two Stray (TSTS) Model on Ability of Process Approach - Andrianingsih, Vivi; Waluya, St. Budi; Sugianto, Sugianto (Unnes Journal of Mathematics Education Research, 2021)
This study aims to determine the ability of mathematical communication in terms of students self-efficacy in learning type two stay two stray (TSTS) cooperative approaches with process skills. The method used in this research is mixed method with concurrent embedded design. This research was conducted in class VII SMPN 40 Semarang in the academic year 2017/2018 with class VII F as an experimental class subjected to cooperative learning model type TSTS approached by process skills and class VII G as a control class subjected to the Problem Based Learning model. Data is collected by tests, questionnaires, observation sheets and interviews. Subject taking techniques based on self-efficacy were taken 2 subjects for each category by random sampling. The results showed that the description of mathematical communication skills in terms of students' self-efficacy varied. This is shown from 7 students with high self-efficacy categories obtained mathematical communication skills in the form of 5 students in the high category and 2 students in the moderate category, from 21 students in the category of self-efficacy being obtained mathematical communication skills results in the form of 8 students in the high category, 11 students in the medium category, and 2 students in the low category, then 4 students in the low self-efficacy category obtained mathematical communication skills in the form of 1 student in the high category, 2 students in the medium category, and 1 student in the low category.